Woman Varayoc of Peruvian Andes - Gutiérrez-Gómez, Edgar; Huanca-Arohuanca, Jesús Wiliam; Quispe-Arroyo, Adolfo; González-Ríos, Rosa Cecilia; Huari-Salazar, Yodel Cheldo (Frontiers in Sociology, 2023)
This study focuses on the importance of the symbolism of social control by the woman as the Varayoc (an office of authority of Incan origin) in a community in the Peruvian Andes. The objective is to explain the survival of the office of the Varayoc—traditionally held exclusively by men—and the acceptance of Andean women to it as a recognition of gender equality. In this field investigation, we interviewed and observed the most important activities of a woman Varayoc administering justice and present in all communal tasks. We conclude that women in the Peruvian Andes are approaching a status of equality with men in their position as the Varayoc, while maintaining the Incan tradition of local governance through the symbolism of the rod of command, which is also called Varayoc. It is evident that more women in the Andean community are interested in assuming political leadership with the symbolism of the ancestral Varayoc.